Alpinia oxyphylla Miq. and Its Active Compound P-Coumaric Acid Promote Brain-Derived Neurotrophic Factor Signaling for Inducing Hippocampal Neurogenesis and Improving Post-cerebral Ischemic Spatial Cognitive Functions - He, Yacong; Chen, Shuang; Tsoi, Bun; Qi, Shuhua; Gu, Bing; Wang, Zhenxing; Peng, Cheng; Shen, Jiangang (Frontiers in Cell and Developmental Biology, 2021)
Alpinia Oxyphlla Miq (AOM) is a commonly used medicinal herb for post stroke treatment but the underlying mechanisms and bioactive compounds for neuroprotective and neurogenic effects remain unknown. In the present study, we tested the hypothesis that AOM could induce adult hippocampal neurogenesis and improve post-stroke cognitive impairment via inducing brain-derived neurotrophic factor (BDNF) signaling pathway in both in vivo rat model of transient middle cerebral artery occlusion (MCAO) ischemia and in vitro cultured neural stem cells (NSCs) under OGD/reoxygenation condition. By using Morris water maze and novel objective recognition test, we found that AOM treatment significantly improved the spatial learning/memory impairment and enhanced cognitive functions in the post MCAO ischemic rats. AOM promoted adult hippocampal neurogenesis and up-regulated the expression of BDNF, TrkB and p-AKT in the hippocampus regions. By using high content screening (HCS) technology and HPLC method, we identified P-coumaric acid (P-CA) is the most effective compound from AOM to induce proliferation of NSCs and activate BDNF/TrkB/AKT signaling pathway in both in vitro and in vivo experiments. The effects of P-CA on inducing BDNF/TrkB/AKT signaling and the NSCs proliferation were abolished by ANA12, a BDNF/TrkB specific inhibitor. Furthermore, P-CA dose-dependently enhanced the NSCs proliferation and differentiation in the hippocampus, improved the spatial learning, increased short and long-term memory and reduced anxiety in the post MCAO ischemic rats. Taken together, we conclude that P-CA is a representative active compound from AOM to promote hippocampal neurogenesis, enhance cognitive functions and reduce anxiety for post ischemic stroke. The underlying mechanisms could be related to activate the BDNF/TrkB/p-AKT signaling pathway.